2004
DOI: 10.1667/rr3114.1
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-Ray-Induced Decomposition of Amino Acids: An XPS, Mass Spectrometry, and NEXAFS Study

Abstract: Decomposition of five amino acids, alanine, serine, cysteine, aspartic acid, and asparagine, under irradiation with soft X rays (magnesium Kalpha X-ray source) in ultra-high vacuum was studied by means of X-ray photoelectron spectrometry (XPS) and mass spectrometry. A comparative analysis of changes in XPS line shapes, stoichiometry and residual gas composition indicates that the molecules decompose by several pathways. Dehydration, decarboxylation, decarbonylation, deamination and desulfurization of pristine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
124
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(145 citation statements)
references
References 50 publications
20
124
1
Order By: Relevance
“…The N1s core level is asymmetric with two maxima at binding energies of 400.1 and 401.7 eV under dry conditions ( figure 9). These binding energies agree well with previously reported values for NH 3 + and NH 2 in phospholipids, proteins and amino acids [17,25], suggesting the presence of deprotonated and, to a lesser extent, protonated NH 2 groups in our experiment. With increasing water vapor pressure, the N1s relative intensity of both peaks changed and the binding energy to 401.4 and 404.3 eV, respectively.…”
Section: Water Interaction With Phospholipid Moleculessupporting
confidence: 93%
“…The N1s core level is asymmetric with two maxima at binding energies of 400.1 and 401.7 eV under dry conditions ( figure 9). These binding energies agree well with previously reported values for NH 3 + and NH 2 in phospholipids, proteins and amino acids [17,25], suggesting the presence of deprotonated and, to a lesser extent, protonated NH 2 groups in our experiment. With increasing water vapor pressure, the N1s relative intensity of both peaks changed and the binding energy to 401.4 and 404.3 eV, respectively.…”
Section: Water Interaction With Phospholipid Moleculessupporting
confidence: 93%
“…The binding energy of electrons in the Zn 2p 3/2 , O 1s, N 1s, and C 1s orbitals was reported to appear at 1,021, 530, 399, and 284 eV, respectively. [23][24][25][26] All the coated ZnO nanoparticles showed strong peaks at the corresponding positions, suggesting the existence of both ZnO and the coating agents. Zn was included in the ZnO nanoparticles, and the O in both the ZnO and coating agents.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…This agrees with XPS studies for several amino acids containing the NH 2 group. 17 A peak at the lower binding energy can be attributed to imino species that include a double N v C bond. 18 This assignment is also in very good agreement with the density functional theory calculations of inner shell ionization energies of imino and amino sites in cytosine and cytidine.…”
Section: A Xps Characterization Of Nucleobasesmentioning
confidence: 99%
“…Mass spectrometric studies on desorption of fragments during soft X-ray induced decomposition of amino acids showed that only low-molecular-mass gaseous species are detected. 23 This can be due to the fact that bigger fragments do not have enough kinetic energy in order to be desorbed. In the present studies on DNA damage, we assume that observed mass loss is due to desorption of small fragments containing N and O atoms, which can be released by simple bond cleavages, e.g., C u NH 2 and C v O bonds, respectively, while fragments that contain C atoms are mostly involved in ring structures.…”
Section: Compositional Changes Of Dna Induced By X Raysmentioning
confidence: 99%